Ulap-Ulap Sebagai Media Seni Sakral Dalam Kebudayaan Bali - I Wayan Hendra Purnawan; Ni Wayan Suantini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Ulap-ulap is one of the sacred arts media in Balinese culture. The caterpillar has an artistic form and holds Hindu theological value in it. Various sacred characters are presented in an anointing (ulap-ulap). Showing a sacred side and influencing the psychology of Hindus to always behave in a good and right way. Hindus in Bali believe that the presence of worms in a building will be able to neutralize the negative effects of the environment, and create a positive atmosphere for the building owner. The use of a white cloth as a basic material for ulcers implies the purity of the heart of the person who builds the building. Buildings for Hindus are not only used as profane media, but also function as sacred media in supporting religious processions. The process of making ulap is carried out by following certain rituals, so that the magical power to be presented in an ulap-ulap can play a role as expected. The existence of ulap-ulap as a sacred art medium in Balinese culture will continue to exist, as long as Hindus in Bali remain obedient to carry out religious ceremonies in accordance with the instructions of religious literature.